Koralmbahn quo vadis – Current State of the new Koralmbahn Line and essential Milestones / Koralmbahn quo vadis – Aktueller Status und wesentliche Meilensteine. Issue 6 (2nd December 2015) - Schneider, Klaus; Egger, Jürgen
Abstract: The 130 km long Koralmbahn line between Graz and Klagenfurt is one of the most significant transport infrastructure projects in Europe. It is part of the new southern route and thus an important link in the Baltic‐Adriatic corridor. The key structure on the Koralmbahn line is the 32.9 km long Koralm Tunnel – but construction of the new high speed line will also require 12 new stations and stops, more than 100 bridges and underbridges as well as numerous further tunnels. In Austrias point of view, the Koralmbahn line will represent a considerable structural improvement, especially for Southeast Austria as an industrial location. The quickest journey time between Graz and Klagenfurt will be considerably reduced from currently almost three hours to 45 minutes, with a simultaneous improvement of accessibility. Die 130 km lange Koralmbahn zwischen Graz und Klagenfurt zählt zu den bedeutendsten Verkehrsinfrastrukturprojekten in Europa. Sie ist Teil der neuen Südstrecke und damit auch wichtiger Bestandteil des Baltisch‐Adriatischen Korridors. Herzstück der Koralmbahn ist der 32, 9 km lange Koralmtunnel – darüber hinaus besteht die neue Hochleistungsstrecke aber auch aus 12 neuen Bahnhöfen und Haltestellen, über 100 Brücken und Unterführungen sowie aus zahlreichen weiteren Tunnelbauten. Aus österreichischer Sicht bedeutet die Koralmbahn speziell für den Wirtschaftsstandort Südösterreich eine entscheidende Strukturverbesserung. So wird die schnellste Fahrzeit zwischen Graz und Klagenfurt von derzeit knapp drei Stunden auf 45 Minuten verkürzt und gleichzeitig die Erreichbarkeit deutlich verbessert.